ANALISIS KESALAHAN SISWA DALAM MENGERJAKAN SOAL STOIKIOMETRI MELALUI LANGKAH POLYA (Jurnal Inovasi Pendidikan Kimia, 2019)
This study aims to analyze the types of errors that are dominant or often occur in students in doing stoichiometry problems through Polya steps. The research was conducted in Semarang State Senior High School 6 with 36 subjects in class X IPA 2 who were then grouped with the criteria of 2 upper group students, 2 middle group students, and 2 lower group students. The study was conducted by giving written tests in the form of description tests and interviews. Based on the results of the study, the more dominant mistakes made by 6 students as research subjects were (i) conceptual errors of 33% due to students not understanding the concepts used to solve the problem. Other mistakes made by students include: (ii) errors using data as much as 3%; (iii) technical errors of 10% due to students not being careful in carrying out calculations; (iv) conclusions as much as 54% because students conclude the final results and students do not check their answers. Therefore, in the learning process the teacher should explain the steps in working on the problem using the Polya step and emphasize the steps of understanding the problem and planning a solution so that the students' mistakes in working on the stoichiometry material problem are not repeated. Students are given more and varied practice exercises to further enhance their understanding of material concepts.